IMPLEMENTING PEER FEEDBACK IN LEARNING RECOUNT TEXT WRITING SKILL: STUDENTS’ ENGAGEMENT AND PERCEPTION - Alfiyani Widyastuti; Maman Suryaman; Nina Puspitaloka (PROJECT (Professional Journal of English Education), 2021)
This study aimed to explore the students’ engagement in implementing the stage of peer feedback in learning recount text writing skill and the students’ perception toward the peer feedback strategy in learning recount text writing skill. This study was collected using qualitative approach which provided descriptive explanation. The subject of this study were four junior high school students. Since these days COVID-19 was still happening, this research didn’t carried out in school instead of through Zoom Meeting for the first meeting and the second meeting at researcher’s place within the health protocols. The instruments of this study were field note and questionnaire. Moreover, the result found that the students engagement in implementing each stage of peer feedback strategy were very good. Furthermore, the students perception toward peer feedback strategy were as follow, (1) peer feedback technique helped them in learning writing recount texts, (2) peers' comments and suggestions had an impact for them to be better in writing recount text, (3) having problems while checking their peers’ works since they were lack of grammatical and limit in vocabullaries. Keywords:  Peer feedback, Writing Recount Text, Students’ Engagement, Students’ Perception